The Littles - Peterson, John Lawrence, 1924-; Clark, Roberta Carter (New York : Scholastic, 1967)
When the Biggs go on a three-month vacation and an untidy family from the city moves into the house, the Littles must take action.
"A Little Apple paperback.".
3.3
3-6
Keywords: Families -- Juvenile fiction; Family life -- Fiction; Fantasy; Family life -- Fiction; Fantastic fiction; Fantastic fiction